2020
DOI: 10.1016/j.knee.2020.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical outcomes of transtibial pull-out repair for medial meniscus posterior root tear: Two simple stitches versus modified Mason-Allen suture

Abstract: using the FasT-Fix all-inside suture device combined with Ultrabraid for stronger repair (FasT-Fix 36 modified Mason-Allen technique, F-MMA) [4]. Furumatsu et al. reported that F-MMA suture 37 configuration obtained better meniscal healing and superior clinical outcomes than single FasT-Fix 38 repairs in patients with MMPRTs [5].Recently, a new simple fixation technique using two simple stitches (TSS) under an expected initial tension was reported [6]. Other studies on transtibial pullout repair using TSS repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…Functional improvement with repair was significantly greater in the most studies comparing it with other treatment of MMPRTs, but there were differences between the different repair techniques. 10,22,29 Moreover, changes in meniscus extrusion affect the clinic outcomes after MMPRTs repair, three studies reported their findings 12,17,19 and the results were similar. Chung et al 12 reported that patients with decreased meniscus extrusion had better surgical outcomes in terms of clinical scores and radiographic findings, indicating the importance of reducing meniscus extrusion.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Functional improvement with repair was significantly greater in the most studies comparing it with other treatment of MMPRTs, but there were differences between the different repair techniques. 10,22,29 Moreover, changes in meniscus extrusion affect the clinic outcomes after MMPRTs repair, three studies reported their findings 12,17,19 and the results were similar. Chung et al 12 reported that patients with decreased meniscus extrusion had better surgical outcomes in terms of clinical scores and radiographic findings, indicating the importance of reducing meniscus extrusion.…”
Section: Resultsmentioning
confidence: 86%
“…[5][6][7][8][9][10][11][12][13][17][18][19][20][21][22]24,[27][28][29][30][31][32] The remaining 133 patients (133 cases) were treated with non-operative methods 11,28 or partial meniscectomy. 5,11,13,27 Among the 14 level III studies(Table 1) included in this review, 3 compared meniscal repair with meniscectomy, 9,13,27 1 compared repair with conservative treatment, 28 9 compared distinct repair groups, such as increased extrusion vs decreased extrusion or repair techniques, [9][10][11][12]17,19,20,22,29 1 cohort study compared the efficacy of non-operative management, meniscectomy, and repair. 11 Meniscal repair resulted in significant improvement in functional outcomes scores in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations